Diagnostic Testing of Learning Difficulties and Remedial Education Intervention for Improving Teaching and Learning in Primary Classes in Sri Lanka - Vithanapathirana, M.V. (My University, 2009)
The need for diagnostic testing and remedial education in primary classroom teaching and learning have been emphasised by educationists since a long time. However, the support that has been extended to teachers in Sri Lanka in this direction is a minimum. The teacher development programmes hardly include a systematic training in Diagnosis or Remedying learning difficulties. The majority of the teacher trainers also lack knowledge and skills in diagnostic testing and remedial teaching and these factors have prevented the implementation of remedial teaching in a systematic manner. Diagnosis of Learning Difficulties and Remedial Education Intervention for Quality Improvement in Teaching and Learning was a national scale action research which addressed a critical issue in education from a developmental perspective. The findings of a number of research studies carried out over the period 1994 -2005 had shown the need for diagnostic testing and remedial intervention at primary level, specifically in Language and Mathematics. A programme for capacity building of teacher educators from 20 leading teacher education institutions for diagnosis of learning difficulties and remediation of learning difficulties was planned in order to carryout an action research in collaboration with teachers in classrooms. The author was the coordinator and the team leader of the action research. Capacity building in Diagnostic Testing and Remedial Teaching of teacher educators at National Colleges of Education, and Teacher Colleges and Universities; Curriculum Developers at the NIE; Teachers and Teacher-trainees was the main aim of the programme. A core group of sixty five academics drawn from different categories of teacher education provider institutions in Sri Lanka collaborated for this mini initiative. The training on diagnostic testing was provided by an international expert. Three Diagnostic Test instruments were prepared for First Language (Sinhala and Tamil), Mathematics, and Nonverbal Skills. Tests were implemented to 1000 Grade 4 students from twenty less popular disadvantaged schools from seven of the nine provinces in Sri Lanka including Northern, Eastern, Southern, Western, provinces which were affected by the Tsunami disaster. Six hundred students were selected for the remedial intervention programme after the analysis of learning difficulties. A range of learning difficulties was identified related to reading, comprehension, writing and problems of concept formation and many etc. It was also found that the students who were with learning difficulties had many psycho- social issues affecting their well being. Almost all of the students were from low socio-economic family backgrounds. Twenty action research groups comprising teacher educators, school teachers and teacher trainees planned and implemented two mini cycles of remedial intervention for eight weeks. The outcomes of the programme yielded many lessons on Diagnostic Testing and Remedial Teaching. The participants gained experience of constructing Diagnostic test items for specific difficulty levels related to selected curriculum content and to assess non-verbal skills. Remedial teaching intervention was an eye opener to many of the participants to realise the importance and to understand the systematic approach to address the learning difficulties of the students including providing for psycho-social support. The outcomes of the study allows to make a strong case to recommend the incorporation of Diagnostic testing and Remedial Teaching approaches in both pre-service as well as in-service teacher development programmes. This study was envisaged with the hope of a national level diagnostic and remedial intervention project to be in place in the long term, covering all Primary schools in the system.